CD169+ macrophages are critical for osteoblast maintenance and promote intramembranous and endochondral ossification during bone repair. (March 2019) - Batoon, Lena; Millard, Susan Marie; Wullschleger, Martin Eduard; Preda, Corina; Wu, Andy Chiu-Ku; Kaur, Simranpreet; Tseng, Hsu-Wen; Hume, David Arthur; Levesque, Jean-Pierre; Raggatt, Liza Jane; Pettit, Allison Robyn
Abstract: Osteal macrophages (osteomacs) contribute to bone homeostasis and regeneration. To further distinguish their functions from osteoclasts, which share many markers and growth factor requirements, we developed a rapid, enzyme-free osteomac enrichment protocol that permitted characterization of minimally manipulated osteomacs by flow cytometry. Osteomacs differ from osteoclasts in expression of Siglec1 (CD169). This distinction was confirmed using the CD169-diphtheria toxin (DT) receptor (DTR) knock-in model. DT treatment of naïve CD169-DTR mice resulted in selective and striking loss of osteomacs, whilst osteoclasts and trabecular bone area were unaffected. Consistent with a previously-reported trophic interaction, osteomac loss was accompanied by a concomitant and proportionately striking reduction in osteoblasts. The impact of CD169 + macrophage depletion was assessed in two models of bone injury that heal via either intramembranous (tibial injury) or endochondral (internally-plated femoral fracture model) ossification. In both models, CD169 + macrophage, including osteomac depletion compromised bone repair. Importantly, DT treatment in CD169-DTR mice did not affect osteoclast frequency in either model. In the femoral fracture model, the magnitude of callus formation correlated with the number of F4/80 + macrophages that persisted within the callus. Overall these observations provide compelling support that CD169 + osteomacs, independent of osteoclasts, provide vital pro-anabolic support to osteoblasts during both bone homeostasis and repair.